Konsep Parenting Pada Anak Usia Dini Menurut Mohammad Fauzil Adhim - Winda Astari; Sariah Sariah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research was motivated by mistakes of parents in educating and raising children and parents who lack of knowledge in educating early childhood. This research aimed at knowing the parenting concept for early childhood according to Mohammad Fauzil Adhim. It was a library research. The primary and secondary data were obtained from books, articles, and journals. The primary data was the works of Mohammad Fauzil Adhim. Documentation technique was used for collecting the data. The data were analyzed by reducing, presenting, verifying, and concluding. The findings of this research showed that the parenting concept for early childhood according to Mohammad Fauzil Adhim could be implemented by introducing Islamic values since early age, raising the soul, building learning attitudes, spurring creative thinking, managing words of prohibition, angering and punishing, and needed good parental attitude in providing education and caring for children from an early age.